HUBUNGAN PENGETAHUAN IBU BEKERJA TENTANG ASI EKSKLUSIF DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS KUOK TAHUN 2017 - Afiah Afiah (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2017)
According to the World Health Organization (WHO) Exclusive breastfeeding coverage as much as 54.3%. Therefore, the World Health Organization recommends all babies need to get colostrum (the milk first and second day) to fight infection, and exclusive breastfeeding for 6 months to ensure adequate infant nutrition. The purpose of this study to determine the relationship of knowledge about exclusive breastfeeding working mothers with exclusive breastfeeding in the working area of the Kuok health centers. Exclusive breastfeeding is breastfeeding without any additional food and beverages for infants aged 0-6 months, even though water is not provided in the stage of exclusive breastfeeding. Design of this research is quantitative. The population in this study were mothers who had given birth to work in the month of February to May 2016 in the working area health centers Kuok totaling 115 respondents. The number of samples in this study were 89 respondents, the sampling technique is simple random sampling. Measuring instrument used was a questionnaire with 20 questions. Analysis of the data used are univariate and bivariate. From this study showed that there is a relationship of knowledge about exclusive breastfeeding working mothers with exclusive breastfeeding factors caused by age (20-35 years), basic education (primary and junior) and the number of children in excess of 3 or grande multipara. With the holding of this research, it is expected to health workers and midwives in health centers working area of the Kuok order to improve further education programs on exclusive breastfeeding and motivating mothers to work in order to give exclusive breastfeeding to their babies.